2021
DOI: 10.1021/acs.est.1c00930
|View full text |Cite
|
Sign up to set email alerts
|

Health Benefits and Costs of Clean Heating Renovation: An Integrated Assessment in a Major Chinese City

Abstract: China has been promoting one of the world’s largest campaigns for clean heating renovation since 2017. Here, we present an integrated cost–benefit analysis in a major prefecture-level city by combining a large-scale household energy survey and PM2.5 exposure measurement, high-resolution chemical transport simulation, and health impact assessment. We find that the completed renovation decreases the share of solid fuels in the heating energy mix from 96 to 6% and achieves a concomitant reduction of cooking solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…It implies that coal combustion plays a dominant role in air pollution in rural and even suburban areas. 51 HONO concentration reaches 10.89 and 9.75 ppb at the DBT and XH sites, respectively, which are about twice that at the BJ site.…”
Section: ■ Results and Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…It implies that coal combustion plays a dominant role in air pollution in rural and even suburban areas. 51 HONO concentration reaches 10.89 and 9.75 ppb at the DBT and XH sites, respectively, which are about twice that at the BJ site.…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…PM 2.5 concentration reaches more than 300 μg m –3 at nighttime with obvious CO and NO peaks at the DBT and XH sites. It implies that coal combustion plays a dominant role in air pollution in rural and even suburban areas . HONO concentration reaches 10.89 and 9.75 ppb at the DBT and XH sites, respectively, which are about twice that at the BJ site.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, a study conducted in a rural region of Northern China showed that 60% of clean energy substitution (electricity or natural gas) remarkably reduced the indoor PM 2.5 concentration from 209 to 125 μg/m 3 . 30 In addition, the completed clean renovation with natural gas or electricity was assumed to reduce the level of personal exposure (PE) to PM 2.5 by 4.2 μg/m 3 in Linfen 31 and predictably prevented 130,000 premature deaths related to exposure to solid fuel emissions in China. 32 For some remote rural areas with insufficient network load, disperse distribution of inhabitation, inadequate source of nature gas, or low economic level, it is difficult to replace the traditional solid fuels with natural gas or electricity in a short time.…”
Section: Introductionmentioning
confidence: 99%